Validation of the Moral Disengagement for Adolescent Dating Violence Prevention Scale With Teacher Trainees. (September 2022) - Baker, Elizabeth; Exner-Cortens, Deinera; Brun, Isabel; Russell-Mayhew, Shelly
Once in the workforce, teachers are often asked to participate in school-based adolescent dating violence prevention efforts. However, our understanding of how willing and able future teachers are to engage in dating violence prevention is limited. This may be due, in part, to the lack of available measurement tools. Understanding willingness before teachers are in the classroom is key to exploring how to help future teachers be more ready and able to engage in prevention efforts once they are in the classroom. Thus, the purpose of the current study was to develop and test a measure that assesses one aspect of teacher trainees' willingness to engage in dating violence prevention efforts: moral disengagement. Using two independent samples of teacher trainees ( N =  400; 64.5% White, 75.0% female, 84.5% heterosexual), we explored the factor structure of the Moral Disengagement for Adolescent Dating Violence Prevention (MD-ADVP) scale. We conducted exploratory factor analysis (Sample 1, n  = 222) and confirmatory factor analysis (Sample 2, n  = 178), and also examined the factor structure across sub-groups and assessed internal consistency reliability and construct validity evidence. Analyses suggest the MD-ADVP is unidimensional, and that this factor structure holds across sub-groups. We found strong evidence of both reliability and construct (convergent and divergent) validity. As hypothesized, scores on the MD-ADVP demonstrated significant negative bivariate associations with scores on three measures of adolescent dating violence prevention-related beliefs, and no association with scores on a measure of weight bias. The MD-ADVP will advance research investigating teacher preparation for adolescent dating violence prevention efforts. For example, use of the MD-ADVP can illuminate whether teacher trainees' moral disengagement is an indicator of future implementation success. Further testing of this measure in racially and gender diverse samples is needed.